Secreted and surface proteome and transcriptome of Opisthorchis felineus - Wong, Yide; Pearson, Mark S.; Fedorova, Olga; Ivanov, Vladimir; Khmelevskaya, Ekaterina; Tedla, Bemnet; Arachchige, Buddhika Jayakody; Reed, Sarah; Field, Matt; Laha, Thewarach; Loukas, Alex; Sotillo, Javier (Frontiers in Parasitology, 2023)
Opisthorchis felineus, Opisthorchis viverrini and Clonorchis sinensis are the most medically important species of fish-borne zoonotic trematodes. O. felineus is endemic to the river plains of Western Siberia and Eastern Europe and it is estimated that more than 1.6 million people could be infected with this parasite. Chronic opisthorchiasis may lead to significant gastrointestinal and hepatobiliary pathology.. This study aims to identify and characterize proteins from the secreted and tegumental proteomes of O. felineus. Adult flukes were collected from experimentally infected hamsters and cultured in vitro in serum-free media. We extracted proteins from different compartments of the O. felineus secretome, including (i) soluble excretory/secretory (ES) products; (ii) secreted 15k-EVs; and (iii) tegument. We also generated a transcriptome using long read sequencing, and when combined with high-resolution mass spectrometry, SDS-PAGE separation and protein digestion, we identified 686, 894, 389, 324 and 165 proteins from the ES, 15k-EVs and the three sequentially extracted tegument (TEG) protein fractions, respectively. We performed in-depth gene ontology and protein family analyses on the identified proteins and discuss comparisons against similar proteome datasets acquired for the SE Asian liver fluke O. viverrini and the Chinese liver fluke C. sinensis. The information from this study will form a biologically relevant dataset of O. felineus proteins that could be used in developing diagnostic and therapeutic tools to manage the human cost of O. felineus infection and its associated co-morbidities.